2020
DOI: 10.1002/lno.11605
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the jelly web: Trophic ecology of gelatinous zooplankton in oceanic food webs of the eastern tropical Atlantic assessed by stable isotope analysis

Abstract: Gelatinous zooplankton can be present in high biomass and taxonomic diversity in planktonic oceanic food webs, yet the trophic structuring and importance of this "jelly web" remain incompletely understood. To address this knowledge gap, we provide a holistic trophic characterization of a jelly web in the eastern tropical Atlantic, based on δ 13 C and δ 15 N stable isotope analysis of a unique gelatinous zooplankton sample set. The jelly web covered most of the isotopic niche space of the entire planktonic ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 78 publications
(106 reference statements)
2
23
0
Order By: Relevance
“…Mucus‐feeding pelagic tunicates are generally considered to be passive grazers, feeding indiscriminately on small particles including bacteria and phytoplankton (Crocker et al 1991; Vargas and Madin 2004). Chi et al (2021), in a comprehensive investigation of the trophic position of gelatinous organisms in the Eastern Tropical Atlantic, reported that salps and pyrosomes exhibit isotopic values matching those of surface seston supporting their trophic classification as primary consumers. As with other pelagic tunicates, D. gegenbauri is an efficient filter feeder that can clear large volumes of water in both low‐ and high‐food concentration environments (Gibson and Paffenhöfer 2000; Lucas and Dawson 2014).…”
mentioning
confidence: 99%
“…Mucus‐feeding pelagic tunicates are generally considered to be passive grazers, feeding indiscriminately on small particles including bacteria and phytoplankton (Crocker et al 1991; Vargas and Madin 2004). Chi et al (2021), in a comprehensive investigation of the trophic position of gelatinous organisms in the Eastern Tropical Atlantic, reported that salps and pyrosomes exhibit isotopic values matching those of surface seston supporting their trophic classification as primary consumers. As with other pelagic tunicates, D. gegenbauri is an efficient filter feeder that can clear large volumes of water in both low‐ and high‐food concentration environments (Gibson and Paffenhöfer 2000; Lucas and Dawson 2014).…”
mentioning
confidence: 99%
“…GZ were traditionally overlooked in ecological studies, as they were presumed to be non-nutritious prey for predators (Arai 2005), and "trophic dead ends" that are not consumed by many higher trophic level species. This paradigm is shifting as recent studies using contemporary sampling and analytical approaches illustrate that GZ serve key ecological roles as predators, prey, particle flux mediators, and sequestrators of carbon (Henschke et al 2016;Choy et al 2017;Hays et al 2018;Chi et al 2021). The trophic links between GZ, known as the "jelly web" (Robison 2004), are complex, as GZ feed on a wide diversity of prey and employ diverse feeding strategies (e.g., active hunters, passive trappers, filter feeders).…”
mentioning
confidence: 99%
“…Such an adaptive management process should rely on ecosystem models and jellyfish stock assessments [31] that determine maximum sustainable yields (MSY), quota allocations, appropriate fishing techniques, bycatch regulations, and fishery opening-closure procedures. In addition, a profound knowledge on the ecological roles of target jellyfish species in marine food webs needs to be obtained and implemented into management strategies [55]. Unfortunately, the present review finds that almost all jellyfish fisheries are managed to increase short-term profits rather than plan for more sustainable long-term goals.…”
Section: Jellyfish Harvestmentioning
confidence: 89%